Male-child syndrome and the agony of motherhood among the Igbo of Nigeria (2007)
The persistence of high fertility among the lgbo of Nigeria is linked to the relative strength of the pronatalist tradition among them. Perceived relative benefits of male children as potential custodians of both identity and lineage have sustained this value over generations. A woman, who achieves recognition and status by the birth of at least one male child, is considered fulfilled and ultimately accorded greater respect relative to her counterparts who do not achieve the same feat. Studies have been focusing on the factors defining this gender preference at the expense of those that still sustain marriages that are "barren" and the tension and agony that characterize the psychological disposition of women in this dilemma. This paper examines the links between patriliny and patriarchy and male child preference, and also how inherent society-created effects of male-childlessness could be ameliorated at family and household levels.